Seeing Migration like a State: The case of irregular Indonesian migrant workers deported from Malaysia - Juliawan, Benny Hari (Anti-Trafficking Review, 2018)
The corridor linking Indonesia with Malaysia is particularly rife with transborder mobility, including large-scale labour migration. While irregularity has long been a major feature of these flows, much of the movement now falls under the migration regimes adopted by Malaysia and Indonesia. Long-established casual migration flows collide with recently codified norms and, as a result, oscillate between regularity and irregularity. This paper explores the following questions: How does the regulatory state view and handle undocumented migrants? How does it interact with established social networks that have facilitated irregular labour migration? Particular attention is given to the distinction between the categories of deportable criminals and victims deserving protection, as ascribed by state actors to certain groups of migrants. Based on interviews with twelve deported Florenese migrant workers, the paper discusses how the Indonesian-Malaysian migration regime seeks to shape mobility. It argues that shifting categorisations reflect political imperatives more than the migrants’ needs that prompt them to migrate in the first place.